Infrared to near-infrared and visible upconversion photoluminescence of LiYbF4：Er3＋ nanorods - 刘旺东 李文斌 唐海波 赵明卓 (中国稀土学报：英文版, 2013)
Colloidal LiYbF4：Er3＋ nanorods were synthesized in all aqueous system which had the ratio of length to diameter of-2. These LiYbF4：Er3＋ nanorods emitted intense upconversion light under excitation of infrared at 1488 nm. Importantly, the intensities of two- and three-photon anti-Stokes upconversion PL bands were observed which were comparable to that of the Stokes emission under excitation with low power density. The plots of excitation power density versus emission intensity indicated that all tile emis- sions centered at 549, 668, and 978 nm took a two-photon upconversion process. However, it could be simply deduced that the energy of two photons of 1488 nm were inadequate to produce a photon of 668 or 549 nm. For this conflict, the shape and saturation effects in the intermediate energy states were introduced to demonstrate the corresponding upeonversion processes.